Anak sebagai Poros Generasi Milenial: Implementasi Peraturan Daerah Nomor 5 tahun 2018 tentang Penyelenggaraan Perlindungan Anak - Satria Adha Utama (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Children are central to the millennial generation's sustainability and the nation's future, making their protection a critical concern. In response, Bengkulu Province established Regional Regulation Number 5 of 2018 on implementing Child Protection to safeguard children's rights and well-being. Objective: This research examines the implementation of child protection policies at the Bengkulu Province Office of Women's Empowerment, Child Protection, and Family Planning (DP3APPKB) by Regional Regulation Number 5 of 2018. Method: This field research study was conducted in 2021 using qualitative methods. Data were collected through documentation, observation, and interviews with relevant stakeholders at the DP3APPKB office. Data analysis was carried out using a descriptive qualitative approach. Result: The findings show that the implementation of child protection at DP3APPKB has been conducted effectively, reflecting efforts to uphold justice for children. Programs and services provided align with the principles outlined in the regional regulation. Conclusion: The DP3APPKB of Bengkulu Province has made significant progress in implementing child protection policies. However, continuous evaluation and community participation remain essential to ensure the sustainability and responsiveness of these efforts. Contribution: This research contributes to the evaluation of regional child protection policies and provides insights for both government institutions and society on the importance of ensuring children's rights as the core of future generational development.